Pan Africanism in the African diaspora an analysis of modern Afrocentric political movements - Walters, Ronald W. (Detroit Wayne State, 1993)
This groundbreaking volume analyzes important case studies of Black political movements since the 1960s and the impact of the movements on the African-American community. Previous studies on this subject have been largely historical in nature, focusing on the thought of nineteenth-century Pan Africanist or early twentieth-century formal Pan African movements, such as those led by W. E. B. Du Bois and Marcus Garvey. In this book, Walters analyzes heretofore largely unaddressed cases in which African-American societies forged connections with others in the Diaspora within the framework of significant political movements. He applies social science theory to the analysis of the cases, based on the proposition that Pan African studies - a subject within the broad field of Africana Studies - is itself very diverse and lends itself to analysis by an unlimited number of modern disciplinary approaches and perspectives. Walters uses the tools of comparative politics for examining similar Black and white social institutions and organizations in the United States and other countries and for creating a "tailored" Pan African perspective as a criteria with which to describe the interactive relationships between the American Black community and Blacks in Britain, South Africa, Brazil, and the Caribbean. He fashions a unique and radically new perspective and model for addressing the age-old question of the African continuum by advancing the notion that Pan Africanism can be about the struggle for community - a struggle not incompatible with efforts to change the State. His is a twenty-first century view of race relations and classes in the post-modern era of capitalism. Pan Africanism in the AfricanDiaspora is broadly a work of political science in that it is concerned with political phenomena and applies methods of analysis from that field. Nevertheless
Includes bibliographical references (p. 431-434) and index.
Keywords: Africans -Politics and government